Edukasi Keamanan Pangan: Deteksi Boraks dalam Jajanan Sekolah di SDIT Al Islah Gorontalo - Taupik, Muhammad; Nurrohwinta Djuwarno, Endah; Adam Mustapa, Mohamad; Aprianto Paneo, Mohamad (State University of Gorontalo, 2025)
Food safety is an important issue that must be considered, especially in children's food consumption. The use of borax in food is still found in various snacks sold in school environments, even though this substance can cause serious health disorders. This community service activity aims to increase awareness among students, teachers, and parents at SDIT Al Islah Kota Gorontalo regarding the dangers of borax in food. The method used is lectures and practical borax detection using turmeric as an indicator. If the food contains borax, the color of the turmeric-stained stick changes from yellow to purple. The results of the activity show an increase in participants' understanding of the dangers of borax, as well as higher awareness in choosing safer food. This education is expected to be an initial step in monitoring children's snacks and reducing the use of borax in food.